Sulfonated chitosan as green and high cloud point kinetic methane hydrate and corrosion inhibitor: Experimental and theoretical studies - Farhadian A.; Varfolomeev M.A.; Shaabani A.; Nasiri S.; Vakhitov I.; Zaripova Y.F.; Yarkovoi V.V.; Sukhov A.V. (2020)
© 2020 Elsevier Ltd In this work sulfonated chitosan (SCS) was introduced as a promising green kinetic methane hydrate and corrosion inhibitor to overcome the incompatibility problem between inhibitors. Evaluation of hydrate inhibition performance of SCS with high-pressure autoclave and micro-differential scanning calorimeter revealed that hydrate formation was delayed 14.3 ± 0.2 times and amount of hydrate formed was decreased to 30 % compared to water. The weight loss experiments showed that SCS provides corrosion inhibition efficiency of 95.6 ± 0.1 at 5000 ppm concentration. SCS is able to increase polarization resistance and decrease corrosion current density according to electrochemical measurements. Study of surface morphology by SEM-EDX and profilometer showed that SCSs suppress corrosion rate and reduce the surface roughness of carbon steel. Quantum chemical study confirmed that the pendant groups caused by chitosan modification interact with carbon steel surface. The findings of this research can provide new opportunities to develop biodegradable materials as KHIs/CIs for flow assurance in oil and gas pipelines.